Measuring hours worked in Germany: Contents, data and methodological essentials of the IAB working time measurement concept - Susanne Wanger; Roland Weigand; Ines Zapf (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2015)
This article presents the IAB working time measurement concept, which determines the hours worked in Germany and their individual components. These statistics are essential for a proper analysis of aggregate labour market trends and cyclical fluctuations. We outline the conceptual and methodological framework of the measurement, which evolves further due to its integration in the system of national accounts and due to innovations to the statistical procedures applied. An overview of single components and their data sources is given, while the resulting time series of hours worked and the volume of work are depicted according to their long run trends, cyclical variation and reaction in the 2008/09 financial and economic crisis. – – Der vorliegende Aufsatz stellt die IAB-Arbeitszeitrechnung vor, die die Arbeitszeit in Deutschland sowie deren einzelne Komponenten ermittelt. Diese Statistiken sind von großer Bedeutung für die umfassende Analyse von Arbeitsmarkttrends sowie von konjunkturellen Entwicklungen. Wir stellen den konzeptionellen Rahmen des Rechenwerks dar, der einerseits durch die Einbindung in die Volkswirtschaftlichen Gesamtrechnungen, andererseits durch Neuerungen in der statistischen Methode laufend weiterentwickelt wird. Es wird ein Überblick über die einzelnen Komponen-ten und deren Datenbasis gegeben, bevor die resultierenden Zeitreihen zu Arbeitszeit und Arbeitsvolumen bezüglich ihrer langfristigen Trends, ihres zyklischen Verhaltens, und ihrer Reaktion auf die Finanz- und Wirtschaftskrise 2008/09 untersucht werden.
Keywords: C82; E01; J2; 330; IAB working time measurement concept; Hours worked; Volume of work; Components; Persons in employment; System of National Accounts